2021
DOI: 10.3389/fgwh.2021.647836
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 in Pregnancy: Fitting Into the Existing Viral Repertoire

Abstract: The risk of viral infection during pregnancy is well-documented; however, the intervention modalities that in practice enable maternal-fetal protection are restricted by limited understanding. This becomes all the more challenging during pandemics. During many different epidemic and pandemic viral outbreaks, worse outcomes (fetal abnormalities, mortality, preterm labor, etc.) seem to affect pregnant women than what has been evident when compared to non-pregnant women. The condition of pregnancy, which is widel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 146 publications
(172 reference statements)
0
1
0
Order By: Relevance
“…Later studies have shown that the majority of pregnant women experience mild disease ( Overton et al, 2022 ). Although SARS-CoV-2 infection during pregnancy is associated with a modest increase in risk of morbidity and pregnancy related complications ( Ciapponi et al, 2021 ; Rajput and Sharma, 2021 ; Male, 2022 ), these complications are mostly restricted to patients with severe disease ( Rajput and Sharma, 2021 ; Male, 2022 ). These patients are at increased risk of cesarean delivery and preterm birth ( Marchand et al, 2022 ), and the risk increases further in those with severe disease and pre-existing risk factors such as older age, obesity and gestational diabetes ( Conde-Agudelo and Romero, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Later studies have shown that the majority of pregnant women experience mild disease ( Overton et al, 2022 ). Although SARS-CoV-2 infection during pregnancy is associated with a modest increase in risk of morbidity and pregnancy related complications ( Ciapponi et al, 2021 ; Rajput and Sharma, 2021 ; Male, 2022 ), these complications are mostly restricted to patients with severe disease ( Rajput and Sharma, 2021 ; Male, 2022 ). These patients are at increased risk of cesarean delivery and preterm birth ( Marchand et al, 2022 ), and the risk increases further in those with severe disease and pre-existing risk factors such as older age, obesity and gestational diabetes ( Conde-Agudelo and Romero, 2022 ).…”
Section: Introductionmentioning
confidence: 99%